Familial adult onset hyperinsulinism due to an activating glucokinase mutation: implications for pharmacological glucokinase activation. (2nd July 2014) - Challis, Benjamin G.; Harris, Julie; Sleigh, Alison; Isaac, Iona; Orme, Steve M.; Seevaratnam, Nandini; Dhatariya, Ketan; Simpson, Helen L.; Semple, Robert K.
Summary Context Glucokinase (GCK) phosphorylates and thereby "traps" glucose in cells, thus serving as a gatekeeper for cellular glucose metabolism, particularly in hepatocytes and pancreatic beta cells. In humans, activating GCK mutations cause familial hyperinsulinaemic hypoglycaemia (GCK‐HH), leading to keen interest in the potential of small‐molecule glucokinase activators (GKAs) as treatments for diabetes mellitus. Many such agents have been developed; however, observation of side effects including hypertriglyceridaemia and hepatic steatosis has delayed their clinical development. Objective To describe the clinical presentation and metabolic profiles of affected family members in a kindred with familial hyperinsulinism of adult presentation due to a known activating mutation in GCK. Design Clinical, biochemical and metabolic assessment, and GCK sequencing in affected family members. Results In the 60‐year‐old female proband, hyperinsulinaemic hypoglycaemia (blood glucose 2·1 mmol/mol, insulin 18 pm) was confirmed following 34 h of fasting; however, abdominal computed tomography (CT), pancreatic MRI, endoscopic ultrasound, octreotide scintigraphy and selective arterial calcium stimulation failed to localize an insulinoma. A prolonged OGTT revealed fasting hypoglycaemia that was exacerbated after glucose challenge, consistent with dysregulated glucose‐stimulated insulin release. A heterozygous activating mutation, p.Val389Leu, in the glucokinase gene (GCK) was found in the proband and four other family members. Of these, two had been investigated elsewhere for recurrent hypoglycaemia in adulthood, while the other two adult relatives were asymptomatic despite profound hypoglycaemia. All three of the available family members with the p.Val389Leu mutation had normal serum lipid profiles, normal rates of fasting hepatic de novo lipogenesis and had hepatic triglyceride levels commensurate with their degree of adiposity. Conclusion Activating GCK mutations may present in late adulthood with hyperinsulinaemic hypoglycaemia and should be considered even in older patients being investigated for insulinoma. Normal circulating lipids, rates of hepatic de novo lipogenesis and appropriate hepatic triglyceride content for degree of adiposity in the patients we describe suggest that even lifelong GCK activation in isolation is insufficient to produce fatty liver and metabolic dyslipidaemia.